Material and Damage Characterization of the Elastoplastic Response of the ek4 Deep Drawing Steel - Barrera-Salas, C; Garcia-Herrera, C (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Although EK4 drawing steel is nowadays widely used to manufacture a great variety of parts, it exhibits a marked normal and planar anisotropy that can make it difficult to control the process during its forming. In order to achieve an accurate description of the elastoplastic material response in sheet forming operations, this work presents a detailed material and damage characterization of EK4 deep drawing steel through a two-step methodology involving both experiments and finite element simulations. Firstly, tensile tests on sheet samples cut along the rolling, diagonal and transverse directions were carried out. The corresponding measurements were used to calibrate the material parameters related to the following modeling approaches adopted in the present study: the Hollomon hardening law, the non-associated Hill-48 phenomenological constitutive model and the anisotropic Hosford-Coulomb ductile fracture criterion. Secondly, this characterization was assessed and validated in the numerical simulation of the technological Erichsen test in which the material is mainly subjected to a biaxial stress state. The obtained predictions show a good agreement when compared with the corresponding experimental measurements of the punch load–displacement curve and thickness radial profile at the final fracture stage of the sample. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.